LOANWORDS IN BARACK OBAMA'S INAUGURAL SPEECH - Muziatun Muziatun; Muzdalifah Mahmud; Fatia Hanapi (English Review: Journal of English Education, 2021)
The purpose of this research is to examine the types of loanwords used in Obama's inaugural speech. The loanword theory of Haugen (loanword, loan blend, and loan shift) and Yule's theory of word creation were adopted in this research. It used a qualitative approach to describe the before-after borrow pattern, the types of loanwords, and the process of word formation. The data indicates that sixteen words are part of loan blend; nine words are part of loan shift; and one word is a loanword. While based on word formation, it is revealed that the borrowing word formation process includes twenty-six words and the derivation word formation process involves sixteen words.